THU0252 Nailfold capillaroscopy in systemic lupus erythematosus: a systematic review and critical appraisal. (15th June 2017) - Wijnant, S; Ingegnoli, F; Melsens, K; Thevissen, K; Keyser, F De; Decuman, S; Deschepper, E; Distler, O; Müller-Ladner, U; Piette, Y; Riccieri, V; Ughi, N; et al.
Abstract : Background: Systemic lupus erythematosus (SLE) is a rheumatic disease with common vascular involvement. Nailfold capillaroscopic changes have been described in SLE. Although, until today there is no clear role yet for capillaroscopy in classifying or staging the disease. Objectives: To systematically review and critically appraise the literature on capillaroscopic changes described in SLE. Methods: A sensitive search, on behalf of the EULAR study group on microcirculation in Rheumatic Diseases, was developed in Web Of Science, PubMed and Embase to identify all original research studies in which SLE patients had capillaroscopy. Two reviewers identified titles, abstracts and full texts. Exclusion criteria were: ACR criteria for SLE were not met, less than 5 patients were included in the study, there was no information on capillaroscopy in SLE, no original research or non-English language. All included articles underwent quality appraisal. Results were summarised according to density, dimensions, morphology, haemorrhages, semi quantitative assessment, qualitative assessment (see table) and correlation of capillaroscopic changes with clinical and laboratory parameters. Results: From 172 articles captured, 36 articles were included in this review. The following capillaroscopic parameters were significantly more prevalent in SLE patients compared to healthy controls (see table): tortuous capillaries, abnormal morphology, haemorrhages, nailfold capillaroscopic score, "non-specific patterns" and "scleroderma like pattern". Hairpin shaped capillaries were significantly more prevalent in healthy controls compared to SLE patients. For clinical and laboratory parameters, Raynaud's phenomenon (RP), gangrene and 24 hours proteinuria were significantly correlated with capillaroscopic changes. Conclusions: This first systematic review on capillaroscopy in SLE attests conclusive significant differences in morphology, haemorrhages, semi quantitative assessment, qualitative assessment and some clinical and laboratory parameters. Further large scale research is ongoing through the EULAR study group on microcirculation in Rheumatic Diseases to further define its role. Disclosure of Interest: None declared